2020
DOI: 10.1186/s12879-020-05681-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis between disease severity and inflammation-related parameters in patients with COVID-19: a retrospective study

Abstract: Background COVID-19 is highly contagious, and the crude mortality rate could reach 49% in critical patients. Inflammation concerns on disease progression. This study analyzed blood inflammation indicators among mild, severe and critical patients, helping to identify severe or critical patients early. Methods In this cross-sectional study, 100 patients were included and divided into mild, severe or critical groups according to disease condition. Cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
145
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(166 citation statements)
references
References 11 publications
14
145
2
5
Order By: Relevance
“…Several clinical studies have reported that hyper-inflammation, accompanied by increased serum levels of pro-inflammatory cytokines and chemokines, is associated with disease severity and death in COVID-19 [ 14 , 20 22 ]. In fact, post-mortem analyses have revealed that high levels of pro-inflammatory cytokines are associated with cellular infiltration of organs such as the lungs, heart and kidney [ 14 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have reported that hyper-inflammation, accompanied by increased serum levels of pro-inflammatory cytokines and chemokines, is associated with disease severity and death in COVID-19 [ 14 , 20 22 ]. In fact, post-mortem analyses have revealed that high levels of pro-inflammatory cytokines are associated with cellular infiltration of organs such as the lungs, heart and kidney [ 14 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine storm may eventually lead to severe illness or death, in both sepsis and as observed in the current COVID-19 pandemic ( 51 , 52 ). Furthermore, levels of IL-6 in severely ill patients were found to have increased significantly and were associated with a poor prognosis ( 53 , 54 ). Corticosteroids and non-steroidal anti-inflammatory drugs are commonly used to treat inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results provide markers that could be potentially be valuable in monitoring the progression of SARS-CoV-2 infection and assessing therapeutic strategies to promote viral clearance and restore normal intestinal function. Among the protein functions described, some such as Galectin-9 and CRP are already under investigation as biomarkers of disease severity [38][39][40] . Interestingly, elevated serum levels of CRP, especially in association with a high concentration of D-dimers, are reported to be indicative of an increased risk of adverse outcomes in COVID-19 41 .…”
Section: Discussionmentioning
confidence: 99%